2020
DOI: 10.24875/ciru.20000363
|View full text |Cite
|
Sign up to set email alerts
|

Manifestaciones extrapulmonares de la infección por SARS-CoV-2

Abstract: La enfermedad causada por un nuevo coronavirus, que inició en 2019, fue denominada COVID-19 y declarada pandemia el 11 de marzo de 2020 por la Organización Mundial de la Salud. Si bien es cierto que los primeros reportes enfatizaron las manifestaciones respiratorias de esta enfermedad como presentación clínica inicial, poco a poco empezaron a aparecer casos con manifestaciones iniciales distintas, involucrando otros sistemas. En los casos en los que se identificó afectación del sistema nervioso central, los ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
0
0
2
Order By: Relevance
“…Studies have shown a great relationship between acute myocardial injury, evidenced by elevated troponin in patients hospitalized for COVID-19 and a worse outcome during hospitalization. In this case, individuals who presented changes in the marker require intensive care, in the vast majority, which is a predictor of higher lethality in patients infected with COVID-19 1,8,10,12,[15][16][17][18]22,24,26 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown a great relationship between acute myocardial injury, evidenced by elevated troponin in patients hospitalized for COVID-19 and a worse outcome during hospitalization. In this case, individuals who presented changes in the marker require intensive care, in the vast majority, which is a predictor of higher lethality in patients infected with COVID-19 1,8,10,12,[15][16][17][18]22,24,26 .…”
Section: Discussionmentioning
confidence: 97%
“…However, studies have shown changes not only in the respiratory system, but also in organs and systems, such as the cardiovascular system. Patients infected with SARS-CoV-2 may develop cardiac pathologies or potentiate existing ones: myocardial lesions, arrhythmias, vascular inflammation, acute myocardial infarction, pulmonary thromboembolism, among others, have already been associated with clinical manifestations of the disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…El sueño favorece la adecuada evolución y recuperación en los enfermos graves. Las alteraciones del sueño afectan con frecuencia a los pacientes hospitalizados en la unidad de terapia intensiva, su causa es multifactorial y se asocia con alteraciones del sistema inmunitario, retardo en los procesos regenerativos, desorganización neurofisiológica, disfunción cognitiva, delirio, incremento en los días de hospitalización y mortalidad (Carrillo-Esper et al, 2017).…”
Section: Deprivación O Fragmentación Del Sueño Y Ruidounclassified
“…Devido a disseminação rápida da doença, em março de 2020 a Organização Mundial da Saúde decretou estado de pandemia. O vírus foi classificado pelo Comitê Internacional de Taxonomia de Vírus como SARS-CoV-2 1 . Faixa etária avançada e comorbidades são considerados fatores predisponentes para altas taxas de letalidade da Covid-19.…”
Section: Introductionunclassified